2015
DOI: 10.1515/nuka-2015-0108
|View full text |Cite
|
Sign up to set email alerts
|

The origin and chronology of medieval silver coins based on the analysis of chemical composition

Abstract: Medieval Central Europe coins - the Saxon coins, also called as the Otto and Adelheid denarii, as well as the Polish ones, the Władysław Herman and Bolesław Śmiały coins - were examined to determine their provenance and dating. Their attribution and chronology often constitute a serious problem for historians and numismatists. For hundreds of years, coins were in uncontrolled conditions and in variable environment. Destructed and inhomogeneous surface were the effect of corrosion processes. Electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The study has demonstrated that isotope analysis provides a signature for a specific workshop or mint, and therefore can be adopted as a technique for the study of ancient coinage and any other class of archaeological bronze metalwork. Our measurements are in agreement with similar investigations performed with different analytical techniques [5,15,16,17,18]. Although our paper would present mainly the potentiality of LAMQS from the point of physical aspects, a tentative of possible attribution of the geological sites of the extracted mineral to the coins can be given.…”
Section: Discussion On the Comparative Analysis With Former Mineralsupporting
confidence: 91%
“…The study has demonstrated that isotope analysis provides a signature for a specific workshop or mint, and therefore can be adopted as a technique for the study of ancient coinage and any other class of archaeological bronze metalwork. Our measurements are in agreement with similar investigations performed with different analytical techniques [5,15,16,17,18]. Although our paper would present mainly the potentiality of LAMQS from the point of physical aspects, a tentative of possible attribution of the geological sites of the extracted mineral to the coins can be given.…”
Section: Discussion On the Comparative Analysis With Former Mineralsupporting
confidence: 91%
“…The analytical examination of silver and silver-plated cultural heritage objects is no exception [5][6][7][8]. Most of the past and present scientific studies of these silver or silver-plated objects, deal with on the examination of coins [9][10][11][12][13][14][15][16][17][18][19][20][21][22], or jewelry [23]from ancient and medieval cultures. Although some studies have been performed on more modern silver alloy objects [24][25][26][27][28], there still exist a void for the study and characterization of electroplated silver objects from the Modernist movement of the late 19 th and early 20 th Century.…”
Section: Introductionmentioning
confidence: 99%